Determination of Silicon Nanofabrication Processes Using Atomic Force Microscopy (AFM) - Shojiro Miyake; Mei Wang; Jongduk Kim (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
This study highlights silicon nanofabrication processes using atomic force microscopy (AFM). Microfabrication is essential for the development of these nanotechnologies but remains challenging. Conventional microfabrication relies on lithography, the most common semiconductor manufacturing technology, which is usually combined with deposition and dry and wet etching processes. The process specifically includes current findings from our lab on mechanical, electrical, and electromechanical processing using an electrically conductive diamond tip, as well as AFM-based silicon nanofabrication by mechanochemical local oxidation by diamond tip sliding. Microscopic three-dimensional manufacturing mainly relies on etching, deposition, and lithography. Therefore, a special emphasis was placed on nanomechanical processes, mechanochemical reactions by potassium hydroxide solution etching, and mechanical and electrical approaches. Several important nanofabrication and surface characterization techniques consisting of scanning probe microscopy such as AFM were also discussed. Nanoscale local oxidation based on these mechanical, mechanochemical, and electrochemical reactions will be applied to future nanodevice processes and nanolithography technology.